2006
DOI: 10.1007/s00423-006-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intra-operative PTH measurement during subtotal parathyroidectomy for tertiary hyperparathyroidism after renal transplantation

Abstract: Background and aims Intra-operative parathyroid hormone (IOPTH) results are not known in the setting of tertiary hyperparathyroidism (HPT) after renal transplantation. Materials and methods A retrospective analysis of 35 tertiary HPT patients who all underwent subtotal parathyroidectomy and IOPTH monitoring was conducted.Results The mean follow-up time was 2.2±1.4 years. Thirty-four patients were cured; one patient (2.8%) had a persistent disease and was cured after reoperation. Median parathyroid hormone (PTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 27 publications
1
43
1
Order By: Relevance
“…A dramatic drop in iPTH levels below normal has been reported after renal transplant and the recovery of normal renal function (17,23). Successful transplantation was performed on 18% of our patients.…”
Section: Discussionmentioning
confidence: 53%
“…A dramatic drop in iPTH levels below normal has been reported after renal transplant and the recovery of normal renal function (17,23). Successful transplantation was performed on 18% of our patients.…”
Section: Discussionmentioning
confidence: 53%
“…The role of intraoperative quick PTH assay in patients with primary HPT [5][6][7] and tertiary HPT after renal transplantation [8,9] is well established and has led to shorter operation times, higher cure rates, and even to minimally invasive parathyroidectomy in selected patients. In contrast to primary hyperparathyroidism, in which adequate resection of hyperfunctioning parathyroid glands can be confirmed by intraoperative PTH monitoring with one of the first-generation immunometric quick iPTH assays, it could not be confirmed in secondary HPT, and it was impossible to correctly predict insufficient reduction of hyperactive parathyroid metabolism and persistent secondary HPT [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the possibility of ectopic and/or supernumerary glands [3,4], parathyroidectomy for secondary HPT always entails uncertainty as to whether all hypersecreting tissue has been removed. Several groups have reported that the results of the intraoperative quick parathyroid hormone (PTH) assay can be used to predict successful outcome of treatment for primary HPT [5][6][7] and tertiary HPT after renal transplantation [8,9]. However, the role of the quick PTH assay in surgery for secondary HPT is unclear because the results cannot be used to accurately determine whether resection of hyperfunctioning parathyroid tissue is complete [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…IOPTH has a high positive predictive value of cure, but a poor negative predictive value in patients with renal HPT [58,97]. Eventually, establishing a predictive capability to assure completeness of resection might guide the surgeon regarding the extent of surgery and the decision of whether to perform a thymectomy.…”
Section: Intraoperative Pth Monitoringmentioning
confidence: 97%